Local wisdom-based instant cream soup as functional emergency food during health crises and disasters - Estuti Wiwit; Wayansari Lastmi; Rahman Nur; Nurul Alfiyah Isnar; Samuel Samuel; Kusmiyati Kusmiyati; Pertiwi Sinar; Rohmatin Etin; Widia Lestari Meti; Enis Rosulina Novi; Asti Rahmawati Vera (BIO Web of Conferences)
Background: The development of functional food with local ingredients of black soybeans and brown rice in the form of cream soup as emergency food is important. These foods have high nutritional content for nutritional preparedness efforts in disaster and health crises. Objective: This study aims to determine the acceptability and nutritional value of three types of cream soup (original flavor, mushroom, and vegetable onion). Methods: There were 236 panelists from 3 provinces (West Java, Yogyakarta, and East Java) for the sensory acceptability test. Nutritional value is measured with HPLC, AAS, or Gravimetric methods according to AOAC (Association of Official Analytical Chemists). Result: The best results for the acceptability of the overall parameter of cream soup in 3 flavors of original (6.6±2.3), mushroom (6.7±2.3), and vegetable onion (7.2±2.4) were in the provinces of West Java. The highest nutritional value of the 3 cream soup variants is found in the mushroom variant with nutritional values of energy (418.14 kcal), protein (12.75 gr), fat (12.65 gr), fiber (15.76 gr), and sodium (1,608 g). Conclusion: The best acceptable product in terms of color, aroma, texture, and taste was the vegetable onion cream soup variant. One portion of cream soup can meet daily energy requirements of 21.5%.